Body dysmorphia in common skin diseases: results of an observational, cross‐sectional multicentre study among dermatological outpatients in 17 European countries. (1st July 2022) - Schut, Christina; Dalgard, Florence J.; Bewley, Anthony; Evers, Andrea W.M.; Gieler, Uwe; Lien, Lars; Sampogna, Francesca; Ständer, Sonja; Tomás‐Aragonés, Lucía; Vulink, Nienke; Finlay, Andrew Y.; Legat, Franz J.; et al.
Summary: Background: Body dysmorphic disorder (BDD) is a common psychiatric disorder associated with high costs for healthcare systems as patients may repeatedly ask for different, often not effective, interventions. BDD symptoms are more prevalent in patients with dermatological conditions than in the general population, but there are no large sample studies comparing the prevalence of BDD symptoms between patients with dermatological conditions and healthy skin controls. Objectives: To compare the prevalence of BDD symptoms between patients with different dermatological conditions and healthy skin controls and to describe sociodemographic, physical and psychological factors associated with BDD symptoms to identify patients who may have a particularly high chance of having this condition. Methods: This observational, cross‐sectional, comparative multicentre study included 8295 participants: 5487 consecutive patients with different skin diseases (56% female) recruited among dermatological outpatients at 22 clinics in 17 European countries, and 2808 healthy skin controls (66% female). BDD symptoms were assessed by the Dysmorphic Concern Questionnaire. Sociodemographic data and information on psychological factors and physical conditions were collected. Each patient was given a dermatological diagnosis according to ICD‐10 by a dermatologist. The study was registered with number DRKS00012745. Results: The average participation rate of invited dermatological patients was 82.4% across all centres. BDD symptoms were five times more prevalent in patients with dermatological conditions than in healthy skin controls (10.5% vs. 2.1%). Patients with hyperhidrosis, alopecia and vitiligo had a more than 11‐fold increased chance (adjusted Odds Ratio (OR) > 11) of having BDD symptoms compared with healthy skin controls, and patients with atopic dermatitis, psoriasis, acne, hidradenitis suppurativa, prurigo and bullous diseases had a more than sixfold increased chance (adjusted OR > 6) of having BDD symptoms. Using a logistic regression model, BDD symptoms were significantly related to lower age, female sex, higher psychological stress and feelings of stigmatization. Conclusions: Clinical BDD symptoms are significantly associated with common dermatological diseases. As such symptoms are associated with higher levels of psychological distress and multiple unhelpful consultations, general practitioners and dermatologists should consider BDD and refer patients when identified to an appropriate service for BDD screening and management.